TANTANGAN DAN PELUANG KONTEN DIGITAL ISLAMI DI ERA GENERASI Z: STUDI KASUS MENGENAI LITERASI DIGITAL PADA PEMUDA HIJRAH SELINGGA - Selvi Amelia; Ahmad Faqih Shofwatullah; Ilham Andika Putra; Rahayu Mega (Sekolah Tinggi Ilmu Tarbiyah (STIT) Lingga, 2024)
Islamic digital content has become a rapidly growing phenomenon among Generation Z, especially with the increasing use of social media and digital platforms. This study aims to analyze the challenges and opportunities of Islamic digital content in shaping digital literacy in youth who are members of the Selingga Hijrah Youth community. The main challenges faced include low digital literacy in critically understanding Islamic content, potential misinformation, and limited knowledge of media ethics among young users. On the other hand, there is a great opportunity to develop Islamic content that is creative, engaging, and relevant to Generation Z's spiritual needs. The research method used is a case study with a qualitative approach through in-depth interviews and content analysis on social media platforms used by the Hijrah Selingga Youth community. The results showed that with good digital literacy, youth could sort and utilize positive Islamic content, build their Islamic identity, and increase their religious knowledge of Islamic principles. This study is expected to contribute to developing effective Islamic digital literacy strategies to strengthen Islamic identity in the digital era.